Influence of Titanium Dioxide Nanoparticles on Microstructure, Electrochemical Corrosion Behavior, Mechanical and Thermal Properties of Sn-Al-Bi Based Alloy - El-Bediwi, Abu Bakr; El-Shishtawi, N.A.; Abdullah, Manal Mawloud (International Journal of Applied Sciences and Biotechnology, 2016)
Effect of adding titanium dioxide nanoparticles on microstructure, Vickers hardness, internal friction, thermal parameters and electrochemical corrosion behavior of Sn76Al10Bi10Cu2Zn2alloy has been studied using different experimental techniques. Crystallinity (peak intensity), crystal size (peak broadness) and orientations (peak position, 2θ) of Sn76Al10Bi10Cu2Zn2alloy changed after adding titanium dioxide nanoparticles. Corrosion resistance and internal friction of Sn76Al10Bi10Cu2Zn2 alloy improved after adding titanium dioxide nanoparticles. Vickers hardness value of Sn76Al10Bi10Cu2Zn2 alloy varied decreased after adding titanium dioxide nanoparticles. Int J Appl Sci Biotechnol, Vol 4(3): 417-424